2013
DOI: 10.1371/journal.pone.0064335
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Functional Measure of Cardiovascular Reserve Predicts Admission to Critical Care Unit following Kidney Transplantation

Abstract: BackgroundThere is currently no effective preoperative assessment for patients undergoing kidney transplantation that is able to identify those at high perioperative risk requiring admission to critical care unit (CCU). We sought to determine if functional measures of cardiovascular reserve, in particular the anaerobic threshold (VO2AT) could identify these patients.MethodsAdult patients were assessed within 4 weeks prior to kidney transplantation in a University hospital with a 37-bed CCU, between April 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…A study involving 10,518 patients undergoing surgery suggested that long-term survival was worse those with AKI, even after complete eGFR recovery (43). We have previously shown a strong association between AKI after endovascular intervention, vascular surgery, renal transplantation or coronary angiography and subsequent short and longterm cardiovascular events and all-cause morbidity, in multiple cohort studies as well as a metaanalysis (4,26,28,29). A recent review from NICE suggests that AKI has a major impact on safety and healthcare-cost (44); a patient with AKI after intervention spends an average of 4.7 extra nights hospitalised with an additional £3,691 for medical-treatment (5,44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study involving 10,518 patients undergoing surgery suggested that long-term survival was worse those with AKI, even after complete eGFR recovery (43). We have previously shown a strong association between AKI after endovascular intervention, vascular surgery, renal transplantation or coronary angiography and subsequent short and longterm cardiovascular events and all-cause morbidity, in multiple cohort studies as well as a metaanalysis (4,26,28,29). A recent review from NICE suggests that AKI has a major impact on safety and healthcare-cost (44); a patient with AKI after intervention spends an average of 4.7 extra nights hospitalised with an additional £3,691 for medical-treatment (5,44).…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding AT was derived using the V-slope method (35). An AT level of 11 ml/min/kg has traditionally been used as a threshold of sufficient CVR in various surgical and other clinical settings (27,29,36). Patients with an AT<11 ml/min/kg are not offered open surgical AAA repair in the institutions involved but will be considered for EVAR.…”
Section: Cardiopulmonary Exercise Testing (Cpet) Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, quantification of cardiovascular reserve through graded exercise has been shown to be powerful given its unique ability to predict the capacity to survive pathologic stresses in various chronic conditions such as heart failure and chronic lung disease 4,[7][8][9] as well as in perioperative demands of major surgeries. [10][11][12] During exercise, alveolar oxygen uptake (VO 2 ) provides the arterial oxygen for delivery to contracting muscles reflecting the coupling of pulmonary gas exchange to cellular respiration by the circulation. 13 Above a certain work rate, exercise sustainability through the aerobic regeneration of ATP is supplemented by anaerobic glycolysis resulting in production of lactic acid.…”
mentioning
confidence: 99%
“…Failure to achieve the target heart rate impairs the capture of sufficient diagnostic information [29] , and ambiguity in correlating ECG findings to territorial ischemia will lead to a decision to pursue additional forms of stress testing in most cases. Testing for functional cardiovascular reserve [30,31] instead may be superior for prognostication although these tests have not been widely adapted. Nonetheless, exercise stress testing is reasonable to pursue in young, otherwise apparently healthy transplant candidates by serving as a positive reinforcement to them.…”
Section: Exercise Stress Testingmentioning
confidence: 99%